PENGARUH PELAKSANAAN PENGAWASAN TERHADAP PRESTASI KERJA KARYAWAN PADA PT. POS INDONESIA (Persero) BENGKULU - Khairul Bahrun; Islamudin Islamudin; Eko Sunandar ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2020)
This study aims to analyze the effect of the implementation of supervision of employee work performance at the Head Office of PT. Pos Indonesia (Persero) Bengkulu. Total samples are 60 peoples. Data collection techniques used in this study were obtained from questionnaires, literature studies, and observations. By using a simple linear regression analysis method, and hypothesis testing (t-test). The results of simple linear regression test obtained the regression equation Y = 6,847 + 0.924X this figure shows the influence of the Supervision variable (X) on the Job Performance variable (Y). After that proceed with using the hypothesis test (t-test) with the results of the t-test that is with tSig for Oversight variable (X) that is equal to 0,000 and a significance of 5% obtained sig = 0.05. So the hypothesis is tested with the criteria that tSig <0.05 (0.000 <0.05) means that H1 is accepted and H0 is rejected. It can be concluded that the Supervision variable (X) has a significant effect on Job Performance (Y) at the Head Office of PT. Pos Indonesia (Persero) Bengkulu. Keyword: pengawasan, prestasi kerja pegawai.